Dietary Energy and Protein Levels During the Prelay Period on Production Performance, Egg Quality, Expression of Genes in Hypothalamus-Pituitary-Ovary Axis, and Bone Parameters in Aged Laying Hens - Xin, Qian; Ma, Ning; Jiao, Hongchao; Wang, Xiaojuan; Li, Haifang; Zhou, Yunlei; Zhao, Jingpeng; Lin, Hai (Frontiers in Physiology, 2022)
Nutrition during the pre-lay period takes effect on the production performance in the laying flock. This study evaluated the effects of dietary energy and protein levels in pre-lay diet on performance during the whole laying period and the egg quality, bone quality, and mRNA expression of hypothalamus-pituitary-gonadal (HPG) axis-related genes of hens at the end of the laying cycle. A total of 1,856 15-wk old Hy-Line brown pullets were randomly assigned to one of the four dietary treatments: using a 2×2 factorial arrangement with 2 energy levels (2,700 and 2,800 Kcal/kg ME, respectively) and 2 protein levels (15%, 16.5% CP, respectively). Pullets were fed ad libitum from 15 to 20 wk and from 20 wk onward, fed with a similar laying diet till 72 wk of age. At 72 wk, the expression of genes in the hypothalamus, pituitary, ovarian, and follicles and bone quality was evaluated. At 72wk, there were no differences in production performance, BW, organ index, and ovarian parameters among the dietary treatments. High-CP diet increased the egg shape index and eggshell thickness (P<0.05), but the eggshell breaking strength, Haugh unit, and albumen height did not differ among the treatments. Neither dietary energy nor protein level took an effect of bone quality. Low-energy diet increased the mRNA expression of gonadotropin-releasing hormone-1 (GnRH-1)in the hypothalamus(P<0.05). The mRNA expression level of estrogen receptor-1 (ESR-1) in the hypothalamus and ovary was elevated by the 2,700ME-15%CP diet (P<0.05). The expression of cytochrome family 17 subfamily A polypeptide 1(CYP17A1) in the large white follicle (LWF), small yellow follicles (SYF) and dominant follicle (DF) was decreased by the 2,800 kcal/kg diet (P<0.05). These results indicate that the prelay diet had no influence on the production performance but had minimal effect on the eggshell characteristics and bone parameters. These results suggest that the energy and protein level of the prelay diet changes the expression of HPG axis-related genes of hens around the end of the laying cycle without changing the circulating sex hormone profile. The effect of prelay diet on the endocrinal adjustment at the end of the laying cycle needs to be investigated further.